"Effect of laser textured dimples on tribological behavior of piston ring and cylinder liner contact at varying load". (2021) - Patil, Atulkumar S.; Shirsat, U.M.
Abstract: Surface texturing is playing a vital role in reduction of friction and wear of sliding components in an engine. The dimple shape, dimple size and area ratio are important texture parameters which needs to be studied for the analysis of friction and wear. The laser surface textured OEM (Original Equipment Manufacturer) piston ring segments with different dimple diameters like 150 µm, 300 µm, 500 µm respectively for spherical dimples and different dimple sizes like 150 µm, 300 µm, 500 µm for square shaped dimples shapes were used for investigating the tribological performance of OEM piston ring and cylinder liner segments at a constant speed of 1500 rpm and load of 80 N and 150 N. A linear reciprocating tribometer was used to investigate the tribological performance of the pair at a temperature of 150 °C with the SAE20W40 engine oil. The results shows that there is reduction in the coefficient of friction by 33.56%, 19.69% and 18.57% for 150 µm, 300 µm and 500 µm dimple diameter piston ring segments respectively. Also the square shaped dimples of size 150 µm, 300 µm and 500 µm were tested at 80 N and 150 N loading conditions and observed that there is sudden reduction in the coefficient of friction for 150 µm and 500 µm textured ring segments due to increase in loading from 80 N to 150 N. The reduction in the coefficient of friction was observed 14.73% and 6.14% respectively for 150 µm and 500 µm respectively. Thus through this work an attempt has been made to investigate the tribological performance of ring and liner pair at simulated conditions with laser textured dimples.